Thinking cancer metaphorically: a sociocultural perspective study on the cancer patients’ narratives - Liaw, Monica Kah-Pei; Collin Jerome, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Cancer is a complex disease that is usually difficult to talk about. Many cancer patients turn to metaphors in describing the disease and their cancer experiences as this allows them to communicate those experiences more effectively. While much research has been carried out on examining the different types of metaphors used by cancer patients, much more needs to be known about the metaphors used by them in relation to their sociocultural background and cognition. This study seeks to address this knowledge gap by examining the metaphors used among cancer patients to describe the disease and their cancer experiences. Most importantly, the study aims to investigate how these metaphors are shaped by the patients’ sociocultural background. Using the Metaphorical Identification Procedure (MIP), the study analysed the data collected from 31 cancer patients from Kuching, Sarawak through semi-structured interview. The results show that the patients turned to “structural”, “conspiracy” and “journey” metaphors and several other metaphors to describe the disease and their cancer experiences. The results also show that the cancer metaphors used by these patients were mostly shaped by their personal life experiences and their sociocultural understanding. The study concludes that the findings could have implications on the current debates over the use of cancer metaphors in oncology and help to drive some recommendations.